Guidelines for the conservative treatment of spinal deformities - Questionnaire for a Delphi consensus - Elif E. Dereli; Shaopeng Gong; Tuğba Kuru Çolak; Deborah Turnbull (AOSIS, 2021)
Background: Spinal deformity is the oldest disease known to humankind. Many types of treatment methods, including both conservative and surgical, are in use. Objective: We aimed to validate a published guideline protocol based on the conservative treatment of spinal deformities. Method: A modified Delphi technique was used with a questionnaire sent out to professionals worldwide regarding the conservative treatment of spinal deformities. Results: Our study was completed after two rounds. A strong level of agreement of 80% and more (consensus cut-off point) was achieved in most questions in the first round. Some statements were below this margin, and they were sent to the participants via email in the second round for re-evaluation. Consensus was achieved in almost all of the statements in the second round. Only two items did not reach the cut-off point but were close to this value. Conclusion: This proposed Guideline Protocol was approved by the participants using the Delphi method and can be used as a valid tool for the conservative treatment of spinal deformities. Clinical implications: A conservative treatment guideline in spinal deformity management, will provide consistency in treatment and will facilitate comparability with surgery. It will be useful in determining the cost-effectiveness of treatment and in choosing the right patient for the right method of treatment. This guideline might help in this context, and may also create a systematic method for clinicians to use as a reference in both research and clinical practice.